A Retrospective Study on Using a Novel Single Needle Cone Puncture Approach for the Iodine-125 Seed Brachytherapy in Treating Patients With Thoracic Malignancy - Li, Fenge; Wang, Liping; Zhang, Yixiang; Feng, Weihong; Ju, Tao; Liu, Zaiping; Wang, Zhenglu; Du, Xueming (Frontiers in Oncology, 2021)
Background: Patients with progressive thoracic malignancy characterized by large irregular tumors with necrosis and life-threatening symptoms lack effective treatments. We set out to develop a single needle cone puncture method for the Iodine- 125 seed (SNCP-125I) brachytherapy, and aim to report the initial results. Methods: 294 patients with advanced thoracic malignancy were treated with local SNCP-125I brachytherapy between March 2009 and July 2020, followed by thorough evaluation of clinical outcome, overall survival (OS), progression-free survival (PFS) and procedure-related complications after treatment. Results: The overall response rate (ORR) amongst the treated patients was 81.0% (238/294). Life-threatening symptoms due to tumor oppression, hemoptysis and large irregular tumor with necrosis were successfully alleviated after the SNCP-125I treatment with a remission rate at 91to 94%. The median OS and PFS were 13.6 months and 5.8 months, respectively. Procedure-related side effects including pneumothorax (32/294), blood-stained sputum (8/294), subcutaneous emphysema (10/294), puncture site bleeding (16/294) and chest pain (6/294) were observed. Patients who were able to follow with chemotherapy or immunotherapy experienced extended OS and PFS, as compared with patients who opted to receive hospice care (16.5 months Vs. 11.2 months). Further pathological and immunological analysis showed that SNCP-125I induced tumor lymphocytes infiltration and long-term tumor necrosis. Conclusion: SNCP-125I brachytherapy effectively eliminates life-threatening symptoms due to local tumor oppression, hemoptysis and large irregular and necrotic tumors in patients with unresectable chest malignancy and significantly induces local tumor regression. SNCP-125I brachytherapy combines with chemotherapy significantly prolong OS and PFS compare with SNCP-125I brachytherapy alone.